2023
DOI: 10.1136/jitc-2023-007552
|View full text |Cite
|
Sign up to set email alerts
|

ONCOS-102 plus pemetrexed and platinum chemotherapy in malignant pleural mesothelioma: a randomized phase 2 study investigating clinical outcomes and the tumor microenvironment

Santiago Ponce,
Susana Cedrés,
Charles Ricordel
et al.

Abstract: BackgroundONCOS-102, an oncolytic adenovirus expressing granulocyte-macrophage colony-stimulating factor, can alter the tumor microenvironment to an immunostimulatory state. Combining ONCOS-102 with standard-of-care chemotherapy for malignant pleural mesothelioma (MPM) may improve treatment outcomes.MethodsIn this open-label, randomized study, patients with unresectable MPM received intratumoral ONCOS-102 (3×1011virus particles on days 1, 4, 8, 36, 78, and 120) and pemetrexed plus cisplatin/carboplatin (from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One is the treatment-related adverse events including some severe reactions such as lymphopenia, and thrombocytopenia, 20 , 329 , and combination with other therapy may increase the risk. 330 It is currently uncertain how OVs caused those adverse events, perhaps related to virus load and tumor necrosis. 331 Several measures have been taken to reduce the virulence and risks of adverse events.…”
Section: Oncolytic Virusmentioning
confidence: 99%
“…One is the treatment-related adverse events including some severe reactions such as lymphopenia, and thrombocytopenia, 20 , 329 , and combination with other therapy may increase the risk. 330 It is currently uncertain how OVs caused those adverse events, perhaps related to virus load and tumor necrosis. 331 Several measures have been taken to reduce the virulence and risks of adverse events.…”
Section: Oncolytic Virusmentioning
confidence: 99%
“…Following these promising results, the phase III INFINITE trial was launched, which is evaluating the efficacy of intrapleural Ad-IFN in combination with celecoxib and gemcitabine in the second-or third-line context, and the results are expected in 2024. ONCOS-102 is a GM-CSF oncolytic adenovirus that demonstrated activity in a phase 1-2 study in combination with cisplatin and pemetrexed [67]. Phase 1 included 15 patients, and it was shown that the administration of the virus was safe and induced immune activation.…”
Section: Vaccinesmentioning
confidence: 99%